Association analyses of more than 140,000 men identify 63 new prostate cancer susceptibility loci - Schumacher, Fredrick R.; Brenner, Hermann; Cuk, Katarina (Nature genetics, 2018)
A large meta-analysis combining genome-wide and custom high-density genotyping array data identifies 63 new susceptibility loci for prostate cancer, enhancing fine-mapping efforts and providing insights into the underlying biology.